ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KACANG METE INDONESIA KE VIETNAM 2018-2019 - Ayuni Agustyan; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
As an agricultural country, Indonesia has been mostly dependent on agricultural sector for majority population main source of revenue and country development. With a large land area, Indonesia has various kinds of plant commodities, one of them is cashew nut. The export of cashew nut could potentially increase the country's foreign exchange if it is exported as a value-added product. Nevertheless, Indonesia as a mainly raw commodity-exporting country has been exporting raw cashew nut mostly to Vietnam and the number of export continued to increase from 2018-2019. The purpose of this research is to identify the reason why Indonesia keep exporting raw chasew nut to Vietnam.This research uses trade theory with state level analysis. This research uses qualitative method and the data source of this research is secondary source that got mainly from book, news, document, article and websites.The result of this research has shown the lack of attention in government’s national program to increase local agricultural products that have the potential to be exported such as cashew nut. There is no recognition in cashew nut industry that has potency such as producing Cashew Nut Shell Liquid (CNSL), demanding local labour, and increaseing selling price. Local and national governments only consider the short term profit by developing local agriculture that has higher economic value by developing corn plants.Keywords: Government, Export, cashew nut, Indonesia, Vietname